Microstructural abnormalities in white and gray matter in obese adolescents with and without type 2 diabetes - Nouwen, Arie; Chambers, Alison L.; Chechlacz, Magdalena; Higgs, Suzanne; Blissett, Jacqueline; Barrett, Timothy; Allen, Harriet A. (Elsevier, 2017)
Aims/hypotheses. In adults, type 2 diabetes and obesity have been associated with structural brain changes, even in the absence of dementia. Some evidence suggested similar changes in adolescents with type 2 diabetes but comparisons with a non-obese control group have been lacking. The aim of the current study was to examine differences in microstructure of gray and white matter between adolescents with type 2 diabetes, obese adolescents and healthy weight adolescents.